PENCATATAN PERKAWINAN DALAM KAJIAN KHI DAN FATWA MUI - Syafar Alim Siregar (Yayasan Baitul Hikmah al-Zain, 2024)
This research is motivated by the fact that we find so many legal irregularities committed in society. For example, there are still many marriages that are carried out by the community but are not recorded with the Marriage Registrar (VAT) at the Religious Affairs Office (KUA), either because of lack of knowledge or ignorance of the importance of the document or because of the intention to get a legal loophole for those who want to carry out polygamy, or also because of the problem of costs in registering marriages for those who cannot afford it. This research uses a literature study study, namely by reading and observing books and writings related to the object of discussion, namely the recording of marriage according to Islamic law, MUI fatwa, and KHI (Compilation of Islamic Law) by looking at rules, principles, and legal doctrines to answer the legal problems that are being faced. The result of the research is the MUI Fatwa regarding the registration of this marriage that an unregistered marriage can be said to be valid, because the unregistered marriage has fulfilled all the principles and conditions of marriage, it's just that they do not record it at the Religious Affairs Office. However, if by not registering the marriage it gets mudharat, then it is haram